2020
DOI: 10.1001/jamaoncol.2020.2965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvant Paclitaxel and Carboplatin on Survival in Women With Triple-Negative Breast Cancer

Abstract: The value of platinum-based adjuvant chemotherapy in patients with triple-negative breast cancer (TNBC) remains controversial, as does whether BRCA1 and BRCA2 (BRCA1/2) germline variants are associated with platinum treatment sensitivity. OBJECTIVE To compare 6 cycles of paclitaxel plus carboplatin (PCb) with a standard-dose regimen of 3 cycles of cyclophosphamide, epirubicin, and fluorouracil followed by 3 cycles of docetaxel (CEF-T). DESIGN, SETTING, AND PARTICIPANTS This phase 3 randomized clinical trial wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 25 publications
3
108
2
Order By: Relevance
“…148 One adjuvant therapy study, mainly in patients with pT1 and node-negative status, showed improved disease-free survival with a carboplatin anthracycline-free combination over epirubicin, fluoro uracil, and cyclophosphamide followed by docetaxel. 149 The carboplatin effect in early breast cancer seems to be independent of BRCA status. 150 To date, PARP inhibitors have not been shown to improve short-term or long-term outcomes in breast cancer.…”
Section: Chemotherapy In Patients With Er-positive Breast Cancer and Tnbcmentioning
confidence: 99%
“…148 One adjuvant therapy study, mainly in patients with pT1 and node-negative status, showed improved disease-free survival with a carboplatin anthracycline-free combination over epirubicin, fluoro uracil, and cyclophosphamide followed by docetaxel. 149 The carboplatin effect in early breast cancer seems to be independent of BRCA status. 150 To date, PARP inhibitors have not been shown to improve short-term or long-term outcomes in breast cancer.…”
Section: Chemotherapy In Patients With Er-positive Breast Cancer and Tnbcmentioning
confidence: 99%
“…Pending a tolerable dose, the combination treatment could be used for both inherent and acquired resistant TNBC with or without selection for basal biomarkers, such as expression of high molecular weight cytokeratins and EGFR1 overexpression. This combination could increase the fraction of patients achieving the benefits of responders to carboplatin in the neoadjuvant 5,6 , adjuvant 45 , and metastatic 46 settings. In conclusion, we show that low dose prexasertib can sensitize carboplatin-resistant TNBC to carboplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, general use in TNBC cannot be recommended (LoE 1aa/A/AGO–) [56]. In TNBC, the question of adding carboplatin as a fourth substance has still not been finally clarified with regard to an OS advantage [57]. However, if an anthracycline-free therapy is chosen, a taxane/platinum combination should be used here (LoE 1b/B/AGO+) [58].…”
Section: Adjuvant Cytotoxic and Targeted Therapymentioning
confidence: 99%